Fonologi Al-Qur'an pada Keserasian Bunyi dalam Surah Maryam: Analisis Bunyi Vokal dan Konsonan - Ferawati, Ferawati; Robbani, A. Syahid; Khalifah, Chyntia Annas; Afidati, Azri (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2025)
The beauty of verses within the Qur’an always invites admiration from anyone who recites and hears it. One of the Qur’an prominent beauty is its linguistic aspects, particularly harmonious sounds that make its reciters and listeners not want to stop. This research aims to reveal the phonological beauty of the Quranic sounding harmony, mainly in Surah Maryam. This study is library research using the Qur’an as primary data. At the same time, the secondary sources are articles in some journals, books, and other library resources. Data were collected using the documentation technique of data collection, then analyzed using coding and descriptive analysis. This research result indicates that the sound harmony within Surah Maryam is in the endings of the 97 verses out of 98. Only the first verse was not harmonious in sound because it contained Muqatha’ah Letters. In addition, sounding harmony in the Qur’an is not necessarily in the endings of each verse, but it could also be in the number of vowels and consonants in each rhyme. Moreover, the sound harmonies functioned as a mark for those not memorizing the Qur'an (reciter or listener) to recognize parts of Surah Maryam.